AVALANCHE MITIGATION USING THE GEOELECTRICAL RESISTIVITY METHOD OF SCHLUMBERGER CONFIGURATION IN TIROMANDA VILLAGE MAKALE SELATAN DISTRICT TANA TORAJA REGENCY - Ibrahim Adhyatma Ismail; Ayusari Wahyuni; Ihsan Ihsan; Hernawati Hernawati; Bergita GM Saka (JURNAL PERTAMBANGAN DAN LINGKUNGAN, 2022)
Mitigation of landslides in Tiromanda sub-district, Makale Selatan sub-district, Tana Toraja district using the shclumberger configuration geoelectrical resistivity method plays an important role in reducing disaster risk. This study aims to determine the distribution of rock lithology in the Tiromanda sub-district, Makale Selatan district, Tana Toraja district. In this study, measurements were made using the geoelectrical resistivity method of the Schlumberger configuration. Measurements were made on 2 tracks with a length of each track is 120 m with the smallest spacing is 1.5 m and the largest spacing is 10 m. The results showed that the lithology in Tiromanda village consisted of three types of rock lithology, namely overburden with a resistivity of 10.7 m – 21.9 m, shale with a resistivity of 157 m – 1955 m, and sediment containing water with a resistivity of 0.484 m – 15.5 m. Based on the results of the analysis of the data indicated as a slip plane at coordinates S 2˚57'13.0" E 119˚55'21.3" with a depth of 5.76 m and the constituent material is shale in fresh condition. Mitigation that can be done is structural mitigation.